In Vitro Anticancer Activity of Phytol on Human Non-Small Cell Lung Cancer A549 Cells - Jie Yu MD; Feng Jin MD; Yingqi Tang PhD; Yumin Huang MD (Integrative Cancer Therapies)
Background: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. Many researchers have previously reported that natural compounds from plants or Chinese Traditional Herbs have a potential to treat NSCLC. But it has not been reported that phytol can treat NSCLC. In this research, we first exposed this effect on A549 cells and researched the mechanism. Methods: In order to evaluate whether phytol has a role in human NSCLC, a human non-tumoral bronchial epithelial cell line (NL20), adenocarcinomic human alveolar basal epithelial (A549) cell line, and NCI-H69 SCLC (H69) cell line were used for related experiments. After determining that phytol had no toxicity to NL20 cells, A549 cells, or H69 cells, the inhibitory effect of phytol on cancer cell related characteristics of cells were determined by luciferase assay, QRT-PCR, proliferation, invasion, and would healing cellular response experiments. Additionally, the quantification of apoptotic cells has been achieved through flow cytometry. Then, bioinformatics was used to establish a database to screen and speculate on phytol’s corresponding targets in lung cancer. Finally, immunoblotting experiments were used to determine the specific pathways affected by phytol. Results: Treatment with phytol at concentrations ranging from 0 to 80 µM for 24 hours was not cytotoxic to the A549 cells and H69 cells. Phytol inhibited AP-1-mediated and NF-κB-mediated luciferase activity in a dose-dependent manner in A549 cells, but not H69 cells. Additionally, phytol significantly inhibited the levels of MMP9, IL-6, VEGFA, IL-8, and NFKBIA in A549 cells, but had no significant effects on H69 cells. Phytol induced significant dose-dependent growth inhibitory effects on A549 cells. A significant decrease in colony formation and migration was observed. Bioinformatic and immunoblotting analysis indicated that phytol inhibited proliferation and migration of A549 cells through the PI3K-Akt signaling pathway. Conclusions: Phytol exhibits anticancer activity by inhibiting PI3K-Akt signaling pathway and may be applicable in the clinical prevention and treatment of lung cancer in the future.